Foreword - EPURE, Manuela (Journal of Economic Development, Environment and People, 2017)
Digital world is changing constantly and the way in which it affects our life and work seems to be dramatically and somehow unpredictable. New skills and competencies are required and more than ever our learning efforts must be equally distributed between old, traditional and new knowledge, more abundant and diverse far from what you learned before and beyond any imagination a decade ago. Performance at work is redefined in such a way that has no connection at all with what was expected from us at the beginning of our working life. We have been trained to use our knowledge to solve problems, now we need to be trained to use machine learning systems to deal with complex problems and to relay on artificial intelligence when it comes about understanding our digital world and his diverse connectivity with our real life.....